Management of Coronavirus Disease 2019 Patients With Lung Cancer: Experience From a Thoracic Oncology Center - Coelho, David Barros; Santos, Vanessa; Araújo, David; Bastos, Hélder Novais; Magalhães, Adriana; Hespanhol, Venceslau; Queiroga, Henrique; Cruz-Martins, Natália; Fernandes, Maria Gabriela O. (Frontiers in Molecular Biosciences, 2021)
Background: Cancer patients appear to be at a higher risk of complications from coronavirus disease 2019 (COVID-19). Specific data related to lung cancer (LC) patients management, active treatment and/or recent diagnosis are still very limited. Here, we aimed to investigate the clinical presentation, baseline features and clinical outcomes of LC patients with COVID-19. Methods: A retrospective case study was performed at Centro Hospitalar Universitário de São Joao (CHUSJ), a tertiary hospital in the North of Portugal. Data from LC patients diagnosed with COVID-19 were collected during the first two months of the COVID-19 pandemic (March-April 2020). Results: A total of 466 patients had consultation (in person or by phone) during the study period at the thoracic oncology centre. Five patients with active LC were diagnosed with COVID-19, being adenocarcinoma the histological type present in all (100%). Most had metastatic stage IV LC (n=3; 60%). Two patients (40%) presented relevant comorbidities, including hypertension, diabetes and heart hailure. For patients undergoing anti-neoplasic treatment, the median time from the last chemotherapy administration to COVID-19 diagnosis was of 4 days (range: 4-39 days). Four patients (80%) were on corticosteroid therapy. All patients needed hospitalization and received oxygen therapy, 2 (40%) of them received high flow nasal cannula with good tolerability and 1 (20%) non-invasive ventilation. Hydroxychloroquine and antibiotics were given to 4 (80%) and 3 (60%) patients, respectively. Three patients (60%) died at a median time of 5 days following COVID-19 diagnosis (range: 2-16 days). Conclusion: This is one of the first studies reporting the adverse outcomes associated with COVID-19 in LC patients at same time that adds evidence regarding the need to create protocols and guidelines to reduce the infection risk in such patients.